Modernism, existentialism, postcriticism: Gabriel Marcel reads Pilgrimage - Guy, A (Dorothy Richardson Society, 2018)
To this day, few traces exist of Dorothy Richardson’s French readership and reception. The facts of translation might imply that this readership and reception were minimal: Pointed Roofs was first translated into French in 1965, eight years after Richardson’s death, and many volumes of Pilgrimage remain untranslated. Of those French readers who did read Richardson in English and in Richardson’s lifetime, perhaps the most prominent was Simone de Beauvoir. In La Force de l’age (1960), her memoir of the period from the late 1920s through to the liberation of Paris in 1944, de Beauvoir describes her reading interests: Besides the books that I read with Sartre, I took in Whitman, Blake, Yeats, Synge, Sean O’Casey, all of Virginia Woolf, tons of Henry James, George Moore, Swinburne, Swinnerton, Rebecca West, Sinclair Lewis, Dreiser, Sherwood Anderson, all the published translations in the ‘Feux croisés’ series, and even, in English, the interminable novel by Dorothy Richardson, that managed across the course of ten or twelve volumes to say absolutely nothing. Whether or not this judgement on Richardson is to be taken negatively or as an existentialist-tinged note of praise, de Beauvoir’s comment is particularly revealing of the context in which Richardson was read in France in the first half of the twentieth century, giving an insight into the French perception of the time of the Anglophone literary field.